Distribution of morphological traits in ornamental peach cultivars according to their priority - L. D. Komar-Tyomnaya (Труды по прикладной ботанике, генетике и селекции)
Background. Distinguishing morphological traits of peach varieties (Prunus persica (L.) Batsch) and their gradations to a greater extent reflect the range of variability characteristic of the peach cultivars grown for fruit. Ornamental peach cultivars have their original features, especially as far as quantitative and qualitative characteristics of the flower are concerned. The use of wild peach and almond species in breeding for decorative purposes significantly widened the range of morphological variation in cultivars and invoked new gradations of their morphological traits. Therefore, it is vital to revise periodically the tables of morphological characters used in the assessment of cultivars. Materials and methods. The work was based on the ornamental peach collection maintained at the Nikita Botanical Gardens. Main morphological traits of cultivars were studied using the peach variety testing guidelines of the Russian State Variety Testing Commission, UPOV Guidelines, the Descriptor List of the Genus Persica Mill., and Expert Examination Methods for Ornamental Peach Varieties. Results. Analysis of the collection according to the main ornamental and morphological traits showed that its diversity in form is represented by 5 grades of tree height, 4 of tree vigor, 5 of tree habit, 10 of corolla color, 5 of double-flowering degree, 9 of flower shape, 4 of leaf color, 8 of flowering time, etc. This allowed us to adjust the tables of morphological characters for describing ornamental peach cultivars when they are assessed for their distinctness, and add new data, namely: 25 new traits with a set of grades and 22 new grades of tree, shoot and flower descriptors, which were absent in the peach testing guidelines of the Russian State Commission and UPOV (1995); 31 traits and 23 grades were added to the new UPOV Guidelines; and 1 trait and 16 new grades to the Expert Examination Methods for Ornamental Peach Varieties. Conclusions. The identified new traits and gradations, which were absent in the previously accepted expert examination procedures, expand the conception of ornamental peach variability. Thirty-one traits characterizing the plant’s overall ornamental appearance during the flowering period were classified as first-priority traits; six of them (tree height, tree habit, flower color, flower shape, double-flowering degree and flowering time) are recommended for classifying cultivars into groups.